2013
DOI: 10.1093/cid/cit768
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Liver Complications in Patients With Hepatitis C Virus-Related Cirrhosis With and Without HIV Coinfection: Comparison of Hepatic Venous Pressure Gradient and Transient Elastography

Abstract: Our data suggest that TE is at least as valid as HVPG for predicting LREs in patients with compensated HCV-related cirrhosis with or without concomitant HIV coinfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 32 publications
5
19
0
Order By: Relevance
“…Our results are largely consistent with those of Pérez-Latorre et al [14], which also confirm an excellent correlation between the value of the hepatic venous pressure gradient and LSM. The authors report 2 cut-offs for predicting absence of liver events (<25 kPa) and presence of liver events (>40 kPa) (first to occur of decompensation or HCC).…”
Section: Prior Studies Of Lsm For Predicting Liver Eventssupporting
confidence: 93%
See 4 more Smart Citations
“…Our results are largely consistent with those of Pérez-Latorre et al [14], which also confirm an excellent correlation between the value of the hepatic venous pressure gradient and LSM. The authors report 2 cut-offs for predicting absence of liver events (<25 kPa) and presence of liver events (>40 kPa) (first to occur of decompensation or HCC).…”
Section: Prior Studies Of Lsm For Predicting Liver Eventssupporting
confidence: 93%
“…This study also showed for the first time that LSM has proven very useful for predicting the development of HCC [14].…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations